The effects of written corrective feedback using wikis among ESL learners - Gharehbagh, Maryam Jazayeri; Siti Hamin Stapa; Saadiyah Darus (Penerbit Universiti Kebangsaan Malaysia, 2019)
Wikis are being used more and more frequently in language learning situations. Their ease of access and usability has made them a popular choice amongst language teachers; especially in the teaching of writing. However, the full potential of wikis outside collaborative writing has yet to be explored. This study aims to focus on the potentials of providing feedback to written work using the platform of wikis. In this study, 14 students were asked to provide feedback and comments on their peers’ essays on a wiki platform using a correction checklist provided to them. These students were first asked to write an essay, upload it onto the wiki platform, and then finally comment on the written texts of their peers; for a total of nine times. At the end of the study, the students’ pre and post-test scores were compared to see whether their written accuracy had improved. A pairedsample t-test was used to analyse the students’ pre and post-test scores and the results showed a significant improvement in Jacob’s (1981) ESL components of content, organization, language use and vocabulary; however, the study did not yield the same results for the students’ punctuation use. In being provided comments by peers and their teacher through the platform of wikis, the students’ enthusiasm increased when put through the feedback; therefore, their focus heightened on writing a more accurate version of their previous essay. This in turn, increased the overall quality of their final essay.